Comparative Effectiveness of Physical Therapy and Electrophysiotherapy for the Treatment of Lateral Epicondylitis: A Network Meta-Analysis. Issue 3 (1st July 2022) - Wood, Shannon M.; Yoon, Alfred P.; Tseng, Hsiao-Jung; Yang, Lan-Yan; Chung, Kevin C.
Abstract : Background: Lateral epicondylitis is a common enthesopathy, possibly caused by overuse and repetitive activity. Although nonoperative management is the primary approach for treating lateral epicondylitis, clinical guidelines and the literature fail to identify the most effective nonoperative treatment. Therefore, the authors conducted a network meta-analysis to compare the effectiveness of physical therapy and electrophysiotherapy treatments for the treatment of lateral epicondylitis. Methods: The authors searched MEDLINE, EMBASE, Web of Science, and Scopus for peer-reviewed randomized controlled trials evaluating the effectiveness of physical therapy and electrophysiotherapy treatments. Data related to article characteristics and outcomes (grip strength and pain visual analog scale score) were collected. Results: Twenty-three clinical trials including 1363 participants (mean age ± SD, 47.4 ± 7.5 years; 53.1 percent women) were included in this study. Pain visual analog scale demonstrated significant reductions in scores after treatment with magnetic field [mean difference (95 percent CI), −1.88 (−2.66 to −1.11)], exercise [−0.90 (−1.69 to −0.1)], and acoustic waves [−0.83 (−1.37 to −0.29)] compared with placebo. For grip strength, no treatment modality was found to be significantly effective. A sensitivity analysis that excluded studies with high publication bias and high degrees of heterogeneity produced similar results to the main analysis with the exception of statistically improved grip strength after light therapy [mean difference (95 percent CI), 5.38 (1.71 to 9.04)] and acoustic wave therapy [7.79 (2.44 to 13.15)]. Conclusions: Electrophysiotherapy treatments should be prioritized over physical therapy. Magnetic field therapy was associated with pain reduction, whereas acoustic wave and light therapy were associated with increased grip strength. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.